Hyperglycemia attenuates fibroblast contractility via suppression of TβRII receptor modulated α-smooth muscle actin expression. Issue 1 (31st December 2022) - Evangelatov, Alexandar; Georgiev, Georgi; Arabadjiev, Borislav; Pankov, Stefan; Krastev, Plamen; Momchilova, Albena; Pankov, Roumen
Abstract: Nonhealing wounds are a common complication in patients suffering from diabetes with hyperglycemia being the most deteriorating factor for this serious pathological condition. Despite the great body of data, the molecular mechanisms by which high glucose affects cellular physiology are still poorly defined. Here we used primary human foreskin fibroblasts cultured in normo- and hyperglycemic conditions to study the mechanisms leading to altered cell contractility. Our results demonstrated that 25 mmol/L glucose effectively reduced fibroblasts ability to contract fibrin gels, and this physiological change was accompanied by a decrease in alpha-smooth muscle actin expression and the percentage of spontaneously differentiated myofibroblasts in the population of high glucose-treated fibroblasts. These changes were a result of hyperglycemia-induced attenuation of TGF-β1 signaling, involving specific suppression of TGF-β receptor type II but not type I expression. Decreased production of the receptor abolished the ability of exogenously added TGF-β1 to induce Smad2/3 phosphorylation in the presence of high glucose concentrations. Our results identify TGF-β receptor type II as hyperglycemia expression-sensitive receptor and add further aspect to the complex way in which high glucose can affect the wound healing process.